Price Effects of Common Ownership in the Seed Sector - Mohammad Torshizi; Jennifer Clapp (The Antitrust Bulletin, 2021)
We investigate the effects of common ownership on firms’ incentives to compete. Using a theoretical model, we illustrate how common ownership changes the nature of competition among firms in the same sector. Our empirical analysis examines these dynamics in the U.S. seed industry and shows that the rise of common ownership concentration is a significant contributor to increase in soy, corn, and cotton seed prices over the 1997–2017 period. These findings contribute to the current literature regarding the anticompetitive effects of common ownership and confirm the result of studies performed in other sectors, such as airlines.